Molecular Imaging, Pharmacokinetics, and Dosimetry of 111In-AMBA in Human Prostate Tumor-Bearing Mice. - Chung-Li Ho; I-Hsiang Liu; Yu-Hsien Wu; Liang-Cheng Chen; Chun-Lin Chen; Wan-Chi Lee; Cheng-Hui Chuang; Te-Wei Lee; Wuu-Jyh Lin; Lie-Hang Shen; Chih-Hsien Chang (Journal of Biomedicine & Biotechnology, 2011)
Molecular imaging with promise of personalized medicine can provide patient-specific information noninvasively, thus enabling treatment to be tailored to the specific biological attributes of both the disease and the patient. This study was to investigate the characterization of DO3A-CH2CO-G-4-aminobenzoyl-Q-W-A-V-G-H-L-M-NH2 (AMBA) in vitro, MicroSPECT/CT imaging, and biological activities of 111In-AMBA in PC-3 prostate tumor-bearing SCID mice. The uptake of 111In-AMBA reached highest with 3.87 ± 0.65% ID/g at 8 h. MicroSPECT/CT imaging studies suggested that the uptake of 111In-AMBA was clearly visualized between 8 and 48 h postinjection. The distribution half-life (t1/2a) and the elimination half-life (t1/2β) of 111In-AMBA in mice were 1.53 h and 30.7 h, respectively. The Cmax and AUC of 111In-AMBA were 7.57% ID/g and 66.39 h*%ID/g, respectively. The effective dose appeared to be 0.11mSv/MBq-1. We demonstrated a good uptake of 111In-AMBA in the GRPR-overexpressed PC-3 tumorbearing SCID mice. 111In-AMBA is a safe, potential molecular image-guided diagnostic agent for human GRPR-positive tumors, ranging fromsimple and straightforward biodistribution studies to improve the efficacy of combinedmodality anticancer therapy.